Last mile deliveries of e-commerce orders: a cross analysis of consumers' ans carriers' perceptions. - Costa, Débora Grassetti Martins da (2020)
The evolution of e-commerce has triggered a true revolution in the market. Due to that, the increase of deliveries changed the urban freight pattern flows and vehicles’ traffic in the cities. These changes have consequences in technological, economic, environmental and social aspects. It is important to highlight that the adoption of good practices and strategies in e-commerce last mile distribution can influence positively the society in general. According to the literature, there is a high potential to use new technologies in the last mile to increase the customer experience, reduce costs, increase security, and support city environmental when delivering e-commerce purchases. Therefore, the aim of this study is to diagnose the e-commerce last mile delivery evaluating new technology solutions proposed by the literature and considering the perceptions from customers and e-commerce carriers. The used method was survey questionnaires applied to consumers and carriers in order to get different perceptions between them in São Paulo city. This region was chosen due to its relevance in the Brazilian demand and complexity in last mile delivery related to productivity, security and urban mobility. Customers and carriers consider more relevant performance and convenience aspects in relation to e-commerce delivery. However, carriers have a greater concern than customers with the points of infrastructure and environment. Demographic and risk data from São Paulo were also analysed and the results support the strategy definition to have pick up points being used to delivery e-commerce purchases in the São Paulo city, predominantly in the most distant areas of the city center.